Diferentes manipulações na amplitude de movimento podem resultar em distintas respostas de força e hipertrofia muscular no treinamento de força? - Gustavo Ferreira Pedrosa (2020)
The range of motion (ROM) is a strength training variable and the impact of its manipulation on strength and muscle hypertrophy responses has been questioned. Thus, the present study aimed to investigate whether ROM manipulation may influence the strength and muscle hypertrophy responses. For this, 45 sedentary women between 18 and 30 years old were equally distributed into four (4) experimental groups and one (1) control group (CON). The experimental groups trained on the “knee extension machine” for three (3) months and had the following ROM denominations and configurations: Full ROM (ACO) - ROM between 100º and 30º of knee flexion (0º = extended knee); Initial Partial ROM (API) - ROM between 100º and 65º; Final Partial ROM (APF) - ROM between 65º and 30º; Varied Range (AVA) - alternation in the ROM configuration of the API and APF groups at each training session. Before and after the training period, all groups underwent panoramic axial images of the rectus femoris and vastus lateralis muscles at four points on the right thigh, between the greater trochanter of the femur and the lateral epicondyle of the femur (40%, 50%, 60% and 70%), using an ultrasound device. Through the images, the cross-sectional area (AST) of each point was calculated and summed among the points. In addition, all groups performed three (3) tests of one maximum repetition (1RM) in the ROM corresponding to the API (initial ROM), APF (final ROM) and ACO (full ROM) groups, before and after the training period to measure and compare the maximum strength performance. All variables were transformed into relative responses (%), with the % increase in AST being understood as indicative of hypertrophy and the % increase in 1RM tests as indicative of increased maximum strength. To compare the strength response and muscle hypertrophy, one two-way ANOVA (Group x Muscle) was used with Kcott-Knott post hoc being used when necessary, and significance level equal to α <0.05. For hypertrophy, the main effect for Group was detected, which API showed the greatest relative increase. ACO and AVA groups showed similar and higher increases than APF and CON, and APF were higher than CON. In the strength response, the significant interaction effect pointed to an ADM-specific strength response (greater increase in trained angles) for the API and APF protocols, which was not seen for the ACO and AVA groups that showed similar increases between 1RM tests. In addition, in the 1RM test at initial ROM the greatest increases were for API and AVA groups. In the 1RM test at the final ROM there were no differences between the experimental groups, and all of them were superior to the CON group. In the 1RM test at full ROM, the ACO, API and AVA groups showed a % similar and greater than APF and CON groups, with APF being higher than CON. Thus the strength and muscle hypertrophy responses are affected by the configuration of the trained ROM.